Effect of elevated temperature on the mechanical properties of high-strain-rate-induced partially damaged concrete and CFSTs. (December 2017) - Mirmomeni, Mahsa; Heidarpour, Amin; Zhao, Xiao-Ling; Packer, Jeffrey A.
Highlights: Concrete and CFSTs have undergone interrupted tests at impact loading rates. Elevated temperature residual mechanical properties of damaged specimen is studied. Residual properties are dependent on level of pre-induced damage and temperature. The effect of pre-deformation loses significance at very high temperatures. X-ray imaging is used to investigate the extent of cracking and crack propagation. Abstract: The present research investigates the effect of high temperatures on the mechanical properties of plain concrete as well as steel-concrete composite samples which have previously sustained partial damage under high-strain-rate loading. With the rise of interest in investigating extreme loading events such as post-impact-fire scenarios, this study will help in evaluating whether partially damaged concrete and composite elements can further sustain additional stresses in case of a subsequent fire outbreak. Unconfined self- compacting concrete (SCC) and SCC-filled mild steel tube (CFST) samples are subjected to a dual-phase testing procedure where they undergo interrupted compressive loading at impact rates of strain, controlled locally at pre-defined damage levels to account for different deformation states. Damaged specimens are subsequently exposed to elevated temperatures and the residual mechanical properties of the samples are measured under quasi-static compression test conditions. Results indicate that for concrete and CFSTs, variation of residual properties is dependent on the level of pre-induced damage as well as exposed temperature, with the effect of pre-deformation losing significance at very high temperatures. Residual characteristics of CFSTs are shown to be reliant on rate and temperature dependency of both constituent materials. Furthermore, X-ray imaging has been utilized to investigate the extent of cracking and crack propagation at different damage levels.